Risk management role in system of Republic Sakha (Yakutia) medicinal maintenance - S. M. Tarabukina; L. V. Moshkovа (Бюллетень сибирской медицины)
With application of expert estimations the most significant factors causing risk for medicinal maintenance of the population, living in certain territorial zones Republics Sakhas (Yakutia) are revealed. The complex of actions for decrease and management of risks in system of medicinal maintenance of republic are scientifically proved and developed. The differentiated approach to formation of trading extra charges on preparations is offered. The design procedure of the size of subventions is developed at preferential medicinal maintenance of the citizens living in remote and sparsely populated areas of republic.